ABUSE AND PRIVATISATION OF STATE POWERS IN LATER PERIODS OF ANCIENT ROME AS A CAUSE OF THE ROMAN EMPIRE’S DEMISE - Deretić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
This paper continues the story about political corruption in the Roman Empire. Towards the end of the Principate, and the beginning of the dominate, the form of rule was changed; at first the principes and then the emperors became absolute or despotic rulers. History offers an array of examples from this period that testify to the conduct of corrupt, cruel rulers whose “lack of restraint finally led to the fall of the Roman Empire”. The emperor became the sole and exclusive ruler of the entire state: he was the legislator, chief of executive power, supreme judge, and commander-in-chief. In terms of formal law, the emperor’s power was unlimited as he was the Lord and God (Dominus et Deus). The state was no longer res publica (public matter) but rather a res privata (private matter) of the emperor. The emperor was aided by a ramified bureaucratic apparatus, whose main characteristic was unreserved loyalty towards the emperor; the officials were appointed and dismissed according to the emperor’s will. In addition to this, incompetency of these officials was frequently apparent and their immediate contact with citizens was marked by fear that they spread through their arbitrariness, proneness to bribery and harshness. Polybius’ phrase that “democracy declines when the government makes people corrupt and greedy” seems to be characteristic of this period, yet it has not lost its topicality even today. As the legislator, the emperor passed such laws as suited him. The full meaning of Tacitus’ thought: “the more laws, the more corrupt the state” came to the fore.